2016
DOI: 10.3892/ijmm.2016.2798
|View full text |Cite
|
Sign up to set email alerts
|

Basic helix-loop-helix transcription factor DEC2 functions as an anti-apoptotic factor during paclitaxel-induced apoptosis in human prostate cancer cells

Abstract: The functions of basic helix-loop-helix (bHLH) transcription factor-differentiated embryonic chondrocyte (DEC)1 (BHLHE40) and 2 (BHLHE41) are involved in various fields such as circadian rhythms, immune responses, cell proliferation, hypoxia reaction as well as malignant tumors. Previous findings showed that DEC served as apoptosis regulators of various cancer cell lines. However, little is known regarding the expression of DEC1 and DEC2 in prostate cancer cells. The present study aimed to examine the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Both DEC1 and DEC2 were later found to repress CLCOK/BMAL1-induced transactivation of the mouse Per1 promoter through direct protein-protein interaction with BMAL1 and/or competition for E-box elements 34 . More recently, the involvement of DEC2 in chondrocyte differentiation from mesenchymal stem cells 3840 as well as cancer cell progression 5658 has also been demonstrated. Strikingly, a recent scRNA-seq study also identified Dec2 as one of the DEGs preferentially expressed in mouse spermatogonia 12 , while its role in germ cells has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Both DEC1 and DEC2 were later found to repress CLCOK/BMAL1-induced transactivation of the mouse Per1 promoter through direct protein-protein interaction with BMAL1 and/or competition for E-box elements 34 . More recently, the involvement of DEC2 in chondrocyte differentiation from mesenchymal stem cells 3840 as well as cancer cell progression 5658 has also been demonstrated. Strikingly, a recent scRNA-seq study also identified Dec2 as one of the DEGs preferentially expressed in mouse spermatogonia 12 , while its role in germ cells has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have indicated a role for BHLHE41 in tumor development, though in different settings, different effects have been observed. Thus, BHLHE41 has been shown to promote oncogenesis in renal and prostate cancer [ 25 , 34 ]. In contrast, in breast, gastric and pancreatic cancer cells, anti-tumorigenic effects have been observed [ 35 – 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on them have focused on embryonic development and tissue differentiation 3. Recent studies have shown that the deregulation of their expression is associated with tumor progression 5 , 7 , 9 , 10 , 12 , 13. Unlike BHLHE40, which is broadly expressed in many tissues, BHLHE41 showed a more restricted pattern of mRNA expression.…”
Section: Discussionmentioning
confidence: 99%